Regulating consent and age capacity in child marriage for Muslims in Malaysia: a legal analysis / Dayang Nur Bahirah Awang Matsni … [et al.] - Awang Matsni, Dayang Nur Bahirah; Ahijman, Amirah Hannan; Tukalan, Diane Sharon; Ahmad Termizi, Muhammad Yazid (Faculty of Law, 2014)
This research focus specifically on child marriage of Muslim in Malaysia as the law relating to the marriage of a non-Muslim are so rigid that there was no vagueness that would open for the possibility of any problem to arise. This research would start by providing the true story behind people's perception on child marriage and the essential elements of child marriage in Malaysia. This research would also provide the laws on child marriage as well as its applicability on the current situation together with the legal position of child marriage in other countries. This research would be concluded with the recommendation on how such issue of child marriage can be resolved in order to reduce the increase number in the problem relating to child marriage as this issue still goes untreated or unsolved unless a certain action are taken or a law are implemented in order to overcome this problem.